Strategi Pengumpulan Zakat Profesi Pasca Pandemi: Tinjauan Manajemen Syariah - Nafia Ilhama Qurratu’aini; Muhammad Wildan Nizarudin; Cynthia Eka Violita (Journal on Education, 2023)
This study aims to analyze the post-covid-19 professional zakat collection strategy from the perspective of sharia management. The research method used a descriptive qualitative approach to obtain overall information, with data collection methods used are observation, interviews, and documentation. The triangulation technique was used to ensure the validity of the research, obtained from informants and concluded by member check. The results of the study show that (1) BAZNAS Kediri City carried out various strategies in collecting professional zakat during the post-pandemic period, namely collaboration with other zakat institutions to deal with the Covid-19 outbreak, csllaboration with the Indonesian Mosque Council to disseminate zakat obligations, distribute brochures and banners and the use of social media as a means of socialization. (2) BAZNAS of Kediri City in implementing the professional zakat collection strategy is in accordance with the principles of sharia management in the functions of planning, implementing and controlling, while the organizing is not fully appropriate because the organizational structure has not been implemented optimally.